Narrative language competence in children and adolescents with Down syndrome - Channell, Marie Moore; McDuffie, Andrea S.; Bullard, Lauren M.; Abbeduto, Leonard (Frontiers in Behavioral Neuroscience, 2015)
This study was designed to examine the narrative language abilities of children and adolescents with Down syndrome in comparison to same-age peers with fragile X syndrome and younger typically developing children matched by nonverbal cognitive ability levels. Participants produced narrative retells from a wordless picture book. Narratives were analyzed at the macrostructural (i.e., their internal episodic structure) and the microstructural (i.e., rate of use of specific word categories) levels. Mean length of utterance, a microstructural metric of syntactic complexity, was used as a control variable. Participants with Down syndrome produced fewer episodic elements in their narratives (i.e., their narratives were less fully realized) than the typically developing participants, although mean length of utterance differences accounted for the macrostructural differences between participant groups. At the microstructural level, participants with Down syndrome displayed a lower rate of verb use than the groups with fragile X syndrome and typical development, even after accounting for mean length of utterance. These findings reflect both similarities and differences between individuals with Down syndrome or fragile X syndrome and contribute to our understanding of the language phenotype of Down syndrome. Implications for interventions to promote language development and academic achievement are discussed.